Gamma-ray emission from massive young stellar objects: the case of IRAS 16547-4247 - Araudo, Anabella Teresa (2008)
The young stellar object IRAS 16547-4247, identified with a massive protostar, presents a highly collimated wind which interacts with the environments. As a result, strong shocks are formed at the jet termination point and particles are accelerated there up to relativistic energies. In the present contribution, the high-energy emission due to non-thermal interactions is calculated.